Prevalence of Procrastination and its Associated Factors with a View to Develop “Task and Time Management Strategies” to Combat Procrastination among Nursing Students - Keshni, Keshni; Aanchal, Aanchal; Yousuf, Afridi; Singh, Aman; Rawat, Ankit; Kaur, Anureet; Wani, Ather (International Journal of Advances in Nursing Management, 2024)
Background: Procrastination is the act of unnecessarily and voluntarily delaying or postponing something. It is a common human experience involving delays in everyday chores. The importance of assessing the prevalence of procrastination and its associated factors with view to develop “Task and Time Management strategies” to combat procrastination among nursing students are preponderant. Moreover, researches have despite that procrastination tends to be significantly higher among students specially those who have difficulty in time management. Objectives: This study was conducted with an object to assess the prevalence of procrastination and its associated factors with view to develop “Task and Time Management strategies” to combat procrastination among nursing students. Materials and methods: An exploratory study was conducted on 750 nursing students in the year of 2023 in selected nursing institutes of state Punjab. The subjects were selected by using quota sampling technique. Modified Procrastination Assessment Scale – Students given by Linda J. Solomon and Esther D. Rothblum in 1994 for assessing the prevalence of procrastination and its associated factors among nursing students. Data was collected by self report (pen and paper) method. Results: This study revealed that out of 750 students most of the nursing students (mean age ± sd=20.43±1.726) showed moderate level of procrastination i.e., 661(88.1%). Others nursing students have 89 (11.9%) have mild procrastination. In reasons for procrastination majority i.e., 90 (12%) of nursing students gave the reason that they had too many other things to do while 77(10.3%) of nursing students procrastinate due to fear of having bad grades. The significant difference between the prevalence of procrastination and socio demographic variables found to be significance with the gender (p=.000), birth order(p=.002). Conclusion: It has been concluded that the most of the students were found to have moderate procrastination and the major reason for procrastination is that nursing students do not want to face the problems as a result of their avoidance they suffer from more stress and anxiety. Gender and birth order have significant association with prevalence of procrastination. Nursing students need to manage time and divide their tasks according to the priority.